Analisis Upah di Perusahaan Industri Printer dan Perlengkapannya di Kabupaten Bekasi Berdasarkan UU Ketenagakerjaan - Risnandar, Aep; Junaedi; Habeahan, Rasman (JOM, 2024)
This research aims to analyze the Determination and Enforcement of Wages in Companies in the Printer and Equipment Industry Sector in Bekasi Regency Based on the Employment Law. The researcher uses a research method with a Normative Juridical approach, namely legal research carried out by examining library materials or mere secondary materials, emphasizing concepts written in statutory or legal regulations which are conceptualized as rules or norms that benchmark human behaviour, this type of research is an analytical description where the author tries to describe the problem of wages in printer companies as the object and location of research, the data used is primary data in the form of statutory regulations such as the Constitution of the Republic of Indonesia, Government Regulations instead of Law Number 2 of 2022 concerning Job Creation which has been stipulated by Law Number 6 of 2023 and Law Number 13 of 2003 concerning Employment. Data analysis is an activity carried out by collecting data, both primary data and secondary data, then arranging it in writing to make it easier to map the problem and then analyzing the data to answer the formulated problem identification. The research results show that the determination of minimum wages in companies in the printer and equipment industrial sector in Bekasi Regency is not by labour law, this can result in legal violations and has the potential to cause dissatisfaction among workers, which in turn can affect company productivity. The implementation of wages and wage scale structure in companies in the printer and equipment industrial sector in Bekasi Regency is not carried out as per the provisions of the Labor Law so that it does not affect the determination and application of workers' wages.